Fermions, scalars and Randall-Sundrum gravity on domain-wall branes - Davies, R; George, D (2007)
We analyse the general features of localisation of fermions and scalars in smoothed field-theoretical versions of the type 2 Randall- Sundrum braneworld model. A scalar field domain-wall forms the brane, inducing warped gravity, and we study the mass spectra of the matter fields in the dimensionally reduced theory. We demonstrate explicitly that both scalar and fermion fields exhibit a continuum of properly normalisable modes starting at zero mass. If discrete bound modes are present in the gravity-free case, these become resonances in the continuum, while off-resonant modes are highly suppressed on the brane. We describe briefly how another scalar field can be used to break a symmetry on the domain-wall while leaving it unbroken far from the wall, as has already been done in the flat space case. Finally we present numerical calculations for a toy model which demonstrates the decoupling of continuum modes at low energies, so the theory becomes four dimensional.